To Be Anxious or Not to be Anxious--That's the Question in Public Speaking - Andrew, Yau-hau Tse (2011)
Phobia of public speaking is a form of social behaviour. Students may underachieve at work or at school because of anxiety and often avoid speaking in classroom settings. They may drop a course which requires a lot of oral presentations. The main objective of this research is to investigate if the teaching of affective learning strategies helps reduce their public speaking anxiety. McCroskey’s (1992) ‘Personal Report of Public Speaking Anxiety (PRPSA) questionnaire was used to collect data on their feelings towards giving a speech. The same questionnaire was administered at the beginning and end of a course in public speaking. Paired T-test was employed to measure the difference of nervousness in the same semester. A total of 202 university technical students majoring in engineering and computing were chosen as subjects. The findings revealed that they significantly experienced less anxiety after they had been taught how to manage their stress. Although this can alleviate their anxiety level, future research is indispensable to evaluate the casual nature of public speaking among university students. Keywords: public speaking anxiety, affective strategies, speech